Causes of Neonatal Re-admission in 24 hours after Cesarean Section - Hayder Abdulsalam Alnakkash; Raid Mohammed Ridha Umran; Alaa Jumaah Manji Nasrawi (مجلة الكوفة الطبية)
Background: According to the American Academy of Pediatrics (AAP), a mother who gives birth to a healthy, term baby should stay in the hospital for as long as necessary to detect any possible issues and give caregivers time to get the child (and family) ready for release. The infant's risk of readmission may be heightened by diagnostic mistakes, or misdiagnosis, and inadequate assessment by healthcare personnel. In order to assess the frequency and cause of hospital readmissions within the first twenty-four hours of life, this study will examine the local pattern of neonatal readmissions in healthy infants. Patients and Methods: This cross-sectional study included 33 neonates who had a c-section birth, after being discharged, and readmission within 24 hours of delivery. The following newborn characteristics were examined: gestational age, birth weight, gender, duration of initial hospital stay (LOS), infant feeding method, and the type of ward from which the neonate was released following the initial evaluation. The following factors related to pregnancy and delivery were evaluated: advanced maternal age (>35 years), low socioeconomic status, low maternal education, high birth order (>2), joint family, rural area residents, primi gravida, premature rupture of membranes (PROM), chorioamnionitis, preeclampsia, diabetes, psychosocial issues, thyroid disorders, and epidural/spinal anesthesia. Results: Sixteen patients out of 33 readmitted neonates were male. the rate of neonatal readmission was 1.34%. Their average birth weight and gestational age were 2918.2 ± 619.2 gm and 36.8 ± 21.72 weeks respectively. They spent 2.62 ± 1.83 hrs. and readmitted at 7.82 ± 5.35 hrs. intervals. The main causes of readmission were vomiting and poor feeding. Regarding the maternal factors; epidural anesthesia and low education was the most significant risk factors. Conclusions: An important component of the quality-of-care consequences of existing discharge rules and procedures may be revealed by this study. We come to the conclusion that vomiting and poor feeding are the main causes of hospital readmission in the first 24 hours of life, necessitating a proper intervention in the early hours of life. The early development of efficient lactation should be the focus of efforts to lessen digestive issues.